2023
DOI: 10.1029/2023ja032200
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed Relativistic Electron Precipitation Patterns Between the Ion and Electron Isotropy Boundaries

A. V. Artemyev,
V. Angelopoulos,
X.‐J. Zhang
et al.

Abstract: Relativistic electron precipitation to the Earth's atmosphere is an important loss mechanism of inner magnetosphere electrons, contributing significantly to the dynamics of the radiation belts. Such precipitation may be driven by electron resonant scattering by middle‐latitude whistler‐mode waves at dawn to noon; by electromagnetic ion cyclotron (EMIC) waves at dusk; or by curvature scattering at the isotropy boundary (at the inner edge of the electron plasma sheet anywhere on the nightside, from dusk to dawn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…An additional feature of this precipitation pattern is that it locates well equatorward from the isotropic <100 keV electron precipitation from the plasma sheet and shows signatures of energy/L-shell dispersion (contours of constant precipitating-to-trapped flux ratio show an energy increase with L-shell increase within [58.5°, 60°], see panels (d, e)). ELFIN detected multiple such events during strong substorms (see Artemyev et al, 2023, for discussions of the energy/L-shell dispersion in EMIC-driven precipitation), the preferable condition for the SAPS formation, confirming that the event from Figures 2 and 3 is not unique, but rather a typical SAPSassociated electron precipitation pattern.…”
Section: 1029/2023gl107731mentioning
confidence: 60%
“…An additional feature of this precipitation pattern is that it locates well equatorward from the isotropic <100 keV electron precipitation from the plasma sheet and shows signatures of energy/L-shell dispersion (contours of constant precipitating-to-trapped flux ratio show an energy increase with L-shell increase within [58.5°, 60°], see panels (d, e)). ELFIN detected multiple such events during strong substorms (see Artemyev et al, 2023, for discussions of the energy/L-shell dispersion in EMIC-driven precipitation), the preferable condition for the SAPS formation, confirming that the event from Figures 2 and 3 is not unique, but rather a typical SAPSassociated electron precipitation pattern.…”
Section: 1029/2023gl107731mentioning
confidence: 60%
“…In contrast, alternate scattering mechanisms of relativistic electrons, principally those by whistler-mode waves and magnetic field line curvature, are not expected to exhibit a similar low energy cutoff in the range between 50 and 1,000 keV. To clarify, we note that 50 keV is the minimum energy of the lowest energy channel of the ELFIN measurements, but otherwise not particularly significant (see details of ELFIN observations of EMIC-driven precipitation events and their comparison with other scattering mechanisms in Angelopoulos et al, 2023;Artemyev et al, 2023;Grach et al, 2022). Statistics of direct measurements of the energy cutoff of precipitating electrons have shown that EMIC waves often drive subrelativistic precipitation well below the theoretical minimum resonance energy for the typical frequency of the observed waves.…”
Section: Introductionmentioning
confidence: 89%
“…The simulation results indicate that the process of FLC scattering exerts on energetic and heavy ions on the nightside, and the ions precipitation driven by FLC scattering mainly occurs in the outer region (L > 4.5) on the nightside. Besides, many previous studies related to FLC scattering mainly focus on the nightside of the terrestrial magnetosphere (Artemyev et al, 2023;Cao et al, 2023;Capannolo et al, 2022;Chen et al, 2023;Dubyagin et al, 2018;Gilson et al, 2012;Ma et al, 2022;Wilkins et al, 2023;Yue et al, 2014;Zhu et al, 2021), which is attributed to the occurrence of the magnetic minimum and the most apparent field line stretching in this region.…”
Section: Introductionmentioning
confidence: 99%